2018
DOI: 10.1111/pde.13514
|View full text |Cite
|
Sign up to set email alerts
|

Lower lip capillary malformation associated with lymphatic malformation without overgrowth: Part of the spectrum of CLAPO syndrome

Abstract: Characteristic lower lip capillary malformation of CLAPO syndrome (Capillary malformation of the lower lip, Lymphatic malformations of the face and neck, Asymmetry, and Partial or generalized Overgrowth) may also occur as an isolated lesion or with only minor anomalies, supporting the concept that there is a spectrum of abnormalities in CLAPO syndrome. Preliminary studies have demonstrated mosaic activating mutations in PIK3CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In contrast to the first description of CLAPO syndrome [1], a recent study found a low frequency of overgrowth in a cohort of 13 patients, suggesting that it should not be considered a major criterion of this entity [2]. Instead, there is a spectrum of abnormalities in CLAPO syndrome, which can present either as an isolated lower lip CM, in association with lymphatic/venous malformations, or as a complete syndrome with asymmetry and overgrowth [2,6].…”
mentioning
confidence: 90%
“…In contrast to the first description of CLAPO syndrome [1], a recent study found a low frequency of overgrowth in a cohort of 13 patients, suggesting that it should not be considered a major criterion of this entity [2]. Instead, there is a spectrum of abnormalities in CLAPO syndrome, which can present either as an isolated lower lip CM, in association with lymphatic/venous malformations, or as a complete syndrome with asymmetry and overgrowth [2,6].…”
mentioning
confidence: 90%
“…Subsequently, other entities have been added to this spectrum. Indeed, PIK3CA mutations have been described in 21 patients with Klippel-Trenaunay syndrome (KTS) (12), in capillary malformation of the lower lip, lymphatic malformations of the face and neck, asymmetry, and partial or generalized overgrowth (CLAPO) syndrome (13), and in diffuse capillary malformation with overgrowth (DCMO) (14).…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…PIK3CA variants exhibit somatic mosaicism and are generally identified only in the affected tissues, often at low minor-allele frequencies [39]. Nonsyndromic children with vascular malformations or epidermal nevi may also have somatic mosaicism for PIK3CA variants limited to the affected tissue [40]. Thus, a molecular diagnosis of PROS may be challenging due to differing levels of mosaicism; a negative molecular result may not necessarily mean absence of the disease.…”
Section: Pik3ca-related Overgrowth Syndromesmentioning
confidence: 99%